Phenolic compounds in two subspecies of Drypis spinosa L. (Caryophyllaceae) in Croatia - Kremer, Dario (Array, 2020)
As a contribution to chemotaxonomic relations, a quantitative analysis of bioactive phenolic compounds was carried out for the first time in Drypis spinosa L. subsp. spinosa and D. spinosa subsp. jacquiniana Murb. et Wettst. ex Murb. in Croatia. Total polyphenols (TP), tannins (T) and total flavonoids (TF) were determined in samples of leaves, stems, and roots using UV-Vis spectrophotometric methods. For the subsp. spinosa, the highest content of TF was in leaves (0.09%), as was the highest amount of TP (2.36%) and T (1.12%). In the subsp. jacquiniana, the highest contents of TF (0.10%), TP (1.96%), and T (0.88%) were measured in stems. Coumaric, ferulic and rosmarinic acid were identified and quantified by HPLC analysis in both subspecies. Quercetin and sinapic acid were identified only in subsp. spinosa, while rutin and naringenin were found only in subsp. jacquiniana. Among them, ferulic acid was identified only in flowers of both subspecies. The results of this study represent a useful basis for further research of phytochemical and eventually phytotherapeutic potential of D. spinosa.